Meningkatkan Kemampuan Bahasa Inggris Mahasiswa melalui Perkuliahan dalam Matakuliah Non-bahasa Inggris - Ali Saukah (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Improving Students' Ability in English through Non-English Courses. The needs for English felt by the university students are more realistic than those felt by the students at the lower levels of education. Their immediate need for English can be realistic when they have to read English textbooks and other references required in their courses. The lecturers of non-English courses have an important role in making the students' need for English realistic. They can make it realistic by assigning the students to do one or all of the following: read textbooks and references written in English, make a 'clipping' of articles written in English relevant to the topics covered in their courses, write papers in Indonesian based on the references and articles they read, and use English as a medium of instruction partially or fully.